From brain injury to classroom: cognitive and academic outcomes after pediatric stroke. A narrative review - Tarantino, Samuela; Proietti Checchi, Martina; Ferilli, Michela Ada Noris; Monte, Gabriele; Borrelli, Alessandro; Tiralongo, Giuseppe; Valeriani, Massimiliano (Frontiers in Neurology, 2025)
Pediatric stroke represents a rare and clinically significant event, often associated with heterogeneous cognitive sequelae. Early brain injury, particularly during the perinatal period, can result in impaired intellectual functioning and various neuropsychological deficits. Cognitive challenges typically affect language, memory, attention, and executive functions, with their nature and severity influenced by factors such as lesion location, age at onset, and comorbidities like epilepsy or sleep disturbances. Language deficits are commonly observed, particularly in cases involving left-hemispheric or basal ganglia damage, and may endure despite neuroplastic adaptation. Executive dysfunction is also frequently observed, typically involving reduced working memory and cognitive flexibility, and is strongly linked to academic underachievement. Moreover, the diagnosis of secondary ADHD may further complicate the cognitive profile, intensifying challenges related to attention, learning, and behavioral regulation. Despite the high need for tailored educational support, evidence-based cognitive rehabilitation strategies remain limited. Emerging interventions – such as non-invasive brain stimulation and virtual reality – have proven promising, but current evidence is preliminary and lacks validation in youth. Given the elevated risk of long-term academic and functional impairment, early cognitive screening and individualized multidisciplinary intervention are essential to support developmental outcomes in children affected by stroke.